Characterization and source of fluorescent dissolved organic matter in the Western Arctic Ocean: new insights from the 2019 summer study - Jeon, Mi Hae; Jung, Jinyoung; Park, Mi Ok; Cho, Kyoung-Ho; Lee, Youngju; Yang, Eun Jin; Kang, Sung-Ho (Frontiers in Marine Science, 2023)
Increase in river discharge and seasonal primary production and decline in sea ice coverage in the Arctic Ocean in summer can significantly affect the distribution and composition of dissolved organic matter (DOM). This study aimed to enhance the current available knowledge about the impacts of environmental changes on the characteristics of DOM in the rapidly changing Arctic Ocean. Seawater samples were collected from the western Arctic Ocean during the summer of 2019 and analyzed for fluorescent DOM (FDOM), dissolved organic carbon (DOC), and stable oxygen isotope (δ18O) content in conjunction with biophysical properties. We identified two humic-like (C1 and C2) and one protein-like (C3) components using fluorescence excitation-emission matrix coupled with parallel factor (EEM–PARAFAC) analysis. Remarkably high intensities of humic-like FDOM were found in the upper halocline layer (32 < salinity < 33.5 psu, at depths between 50–200 m) with high inorganic nutrient concentrations and low N* values, indicating that the humic-like FDOM was supplied from the shelf sediment. Furthermore, shoaling of the upper halocline layer brought high levels of humic-like FDOM to the euphotic zone, resulting in an increased probability of photodegradation of humic-like FDOM due to exposure to solar radiation in the surface layer. Tryptophan-like FDOM was positively correlated with river water fraction (friver) and riverine DOC but not with chlorophyll-a (Chl-a) and heterotrophic bacterial abundance, indicating river discharge as a potential additional source of tryptophan-like FDOM. The correlation coefficients between tryptophan-like FDOM and river water parameters (friver and riverine DOC) differed across the Chukchi Sea, Chukchi Borderland, and East Siberian Sea, implying that the influence of river discharge on tryptophan-like FDOM is region-dependent. An increase in river discharge in future might lead to a greater supply of tryptophan-like FDOM, impacting the dynamics of DOM cycling in the western Arctic Ocean.